Differences in Cytochrome P450-Mediated Pharmacokinetics Between Chinese and Caucasian Populations Predicted by Mechanistic Physiologically Based Pharmacokinetic Modelling - Barter, Zoe E.; Tucker, Geoffrey T.; Rowland-Yeo, Karen (Clinical pharmacokinetics, 2013)
Background International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) guidelines emphasize the need for better understanding of the influence of ethnicity on drug response to minimize duplication of clinical studies, thereby expediting drug approval. Objectives We have developed a Chinese database for the prediction of differences in the population kinetics of drugs mainly metabolized by cytochromes P450 (CYPs) relative to Caucasian populations. Such predictions should help to inform the need for duplication of in vivo pharmacokinetic studies in the two ethnic groups and the design of such studies. Methods Demographic and physiological data for Chinese, along with information on CYP abundances and the frequencies of associated genetic polymorphisms in Chinese, were collated from literature sources and incorporated within the Simcyp Population-based Simulator ® (v11.1). Default Simcyp parameter values for a virtual Caucasian population and for model compounds metabolized principally by specific CYPs were used as the point of reference. The drugs and the main CYPs involved in their metabolism were phenacetin (CYP1A2), desipramine (CYP2D6), tolbutamide (CYP2C9), omeprazole (CYP2C19), and alprazolam and midazolam (CYP3A). Hydroxy bupropion formation was used as a more sensitive marker of CYP2B6 activity than bupropion kinetics. Observed plasma drug concentration–time profiles and pharmacokinetic parameters after oral and, where possible, intravenous dosing were obtained from published in vivo studies in both Chinese and Caucasian subjects. Virtual subjects generated within Simcyp were matched to the subjects used in the in vivo studies with respect to age, sex, dosage and, where possible, CYP phenotype frequency. Predicted and observed plasma drug concentrations and weight-normalized clearances were compared between the ethnic groups. Results Significant differences were identified between Chinese and Caucasian populations in the frequency of CYP2C19 poor metabolizers (PMs) [Chinese 13 %; Caucasian 2.4 %], CYP2D6 PMs and intermediate metabolizers (IMs) [Chinese PMs 0.3 %, IMs 39 %; Caucasian PMs 8 %, IMs <1 %], the hepatic abundance of CYP2C19 (mean values: Chinese 8 pmol/mg; Caucasian 14 pmol/mg) and liver weight (mean values: Chinese 1198 g; Caucasian 1603 g). The observed plasma drug concentration–time profiles and weight-normalized clearances were predicted with reasonable accuracy (100 % within twofold; 89 % within 1.5-fold) in both ethnic groups. The predicted phenacetin, tolbutamide, omeprazole, desipramine, midazolam (intravenous), midazolam (oral), alprazolam (intravenous) and alprazolam (oral) clearances were 36, 25, 51, 43, 24, 17, 21 and 22 % lower, respectively, in Chinese than in Caucasians; the observed clearances were 28, 2, 75, 42, 19, 62, 20 and 21 % lower, respectively. Predicted and observed formation of hydroxy bupropion was lower in Caucasians than in Chinese (6 and 20 %, respectively). Differences between ethnic groups were less after normalization for body weight. Conclusion The results of this study indicate the value of simulation based on mechanistic physiologically based pharmacokinetic modelling (PBPK) in anticipating the likely extent of any differences in the kinetics of CYP substrates in Chinese and Caucasian populations arising from demographic, physiological and genetic differences.